Correlation between acute ischemic stroke onset with Alberta stroke program early CT score - Nasution, Iskandar; Surbakti, Khairul Putra; Lubis, Netty Delvrita; Ekayana, Etiya (International Journal of Research in Medical Sciences, 2020)
Background: Alberta Stroke Program Early CT Score (ASPECTS) is a valid method for assessing early ischemic changes in the middle cerebral artery from a CT scan of patient with acute ischemic stroke. One of the factors that influence ASPECTS is stroke onset time, where a very subtle level of hypodensity in early onset can provide poor reliability on ASPECTS assessments. Aim of the study was to determine the relationship between the onset of acute ischemic stroke and ASPECTS. Methods: This study used a cross-sectional design with Chi-Square method in patients with acute ischemic stroke and anterior circulation stroke treated in The Stroke Corner and Integrated Ward of Haji Adam Malik General Hospital during the months of February - May 2019. All patients were evaluated for ASPECTS and stroke onset at admission. Stroke onset was divided into 3 parts: Under 24 hours, 24 - <48 hours and 48-72 hours. ASPECTS value was assessed by 2 observers. Authors categorized the ASPECT value into 2 groups: Low (≤7) and High (˃7). Results: Among 36 patients with Acute Ischemic Stroke, mean age was 55.7±13.9 years old, which male and female shares equal number by 18 persons (50%). Mean ASPECTS score was 7.2±2.0. This research found 5 patients (13.9%) with less than 24 hours onset and low ASPECTS score, 3 patients (8.3%) with 24 - <48 hours onset and low ASPECTS score, 7 patients (19.4%) with 24 - <48 hours onset and high ASPECTS score, 8 patients (22.2%) with 48-72 hours onset and low ASPECTS score, and 2 patients (5.6%) with 48-72 hours of onset and high ASPECTS score. Valuation of ASPECTS from both observers was considered as excellent (statistic K value = 0.9). Conclusions: ASPECTS has a significant relationship with stroke onset (p=0.029) and the initial ischemic change will be seen more clearly with increasing stroke onset time.